Assessing the Role of Sustainability and ESG Accounting in Driving Corporate Performance and Stakeholder Value - Marani, Yohanes (Yayasan Pendidikan Bukhari Dwi Muslim, 2024)
This study investigates the integration of sustainability principles and Environmental, Social, and Governance (ESG) accounting into corporate strategies and its implications for corporate performance and stakeholder value. Through a comprehensive literature review, the research aims to elucidate the critical role of sustainability and ESG integration in driving long-term value creation and stakeholder engagement. The research methodology adopts a qualitative approach, analyzing existing literature to explore key themes, concepts, and empirical findings related to sustainability integration. Findings reveal that sustainability integration is imperative for mitigating risks associated with climate change, resource depletion, and social inequality, while ESG accounting enhances transparency, accountability, and value creation within organizations. However, challenges such as internal stakeholder resistance, lack of senior management buy-in, and resource constraints hinder effective integration. The discussion emphasizes the need for a holistic approach to sustainability, strong corporate governance, and proactive leadership to overcome implementation barriers and drive sustainable business outcomes. Overall, this research contributes to theoretical understanding by synthesizing insights from diverse perspectives and offers practical implications for companies aiming to prioritize sustainability in their strategic decision-making processes.